The dialectic philosophy of Right and The Good Approaching the Problem from the Perspective of the Quranic Discourse - Zureikat, Zaid; Abu Zureik, Ali (Jordan Journal of Islamic Studies, 2023)
This research aims to extrapolate the curriculum of the holy Quran in the discourse in general, and knowing the farthest goal of the Quranic discourse in particular, is it the abstract right or right for the good of the suitors and their benefit? The Quranic discourse emulates the circumstance, of the nation addressed, in it’s historical and in its continuous dimension over time. The research begins from the doctrine of the nation that all that is issued by God is Right. To find out the answer we have to analyze the words of God to arrive at a conclusion stating which of both theories is correct: Is it the theory of right for the right or the right for the good of the addressed people? In the second case, the words of God must start according to the conditions of the nation as they were the day the prophet was sent. It would then continue to progress with them as long as they follow the instructions and grow with every new directive. And every time God liberates them from inappropriate behavior and directs them to a better and loftier alternative. God may also cancel the rule after achieving its original benefit, and replace it with a different rule that better suits the new phase that has arrived. God teaches them what they may need in the new circumstances which they never practiced before because the problems addressed by the Quranic discourse are human problems wherever and wherever they exist. The research concluded that right and good go hand in hand, That the purposes of right is good, and that the Almighty sent the Book with right, which benefits the addressed people, and for their good.